From Macroscopy to Ultrastructure: An Integrative Approach to Pulmonary Pathology - Verleden, Stijn E.; Braubach, Peter; Werlein, Christopher; Plucinski, Edith; Kuhnel, Mark P.; Snoeckx, Annemiek; El Addouli, Haroun; Welte, Tobias; Haverich, Axel; Laenger, Florian P.; Dettmer, Sabine; Pauwels, Patrick; et al. (Frontiers in Medicine, 2022)
Pathology and radiology are complimentary tools, and their joint application is often crucial in obtaining an accurate diagnosis in non-neoplastic pulmonary diseases. However, both come with significant limitations of their own: Computed Tomography (CT) can only visualize larger structures due to its inherent – relatively – poor resolution, while (histo) pathology is often limited due to small sample size and sampling error and only allows for a 2D investigation. An innovative approach of inflating whole lung specimens and subjecting these subsequently to CT and whole lung microCT allows for an accurate matching of CT-imaging and histopathology data of exactly the same areas. Systematic application of this approach allows for a more targeted assessment of localized disease extent and more specifically can be used to investigate early mechanisms of lung diseases on a morphological and molecular level. Therefore, this technique is suitable to selectively investigate changes in the large and small airways, as well as the pulmonary arteries, veins and capillaries in relation to the disease extent in the same lung specimen. In this perspective we provide an overview of the different strategies that are currently being used, as well as how this growing field could further evolve.